Thomas a Kempis's "De imitatione Christi" and Alexander de Villa "Dei's Doctrinale" - Hofman, Rijcklof (Ons geestelijk erf, 2021)
Thomas a Kempis wrote his Imitatio Christi in a polished style, with much consideration for detail and the careful wording of his message. In order to do so he made ample use of figurative language, and he showed great familiarity with figures of speech. He must have become acquainted with these while following secondary education in the city school in Deventer. In this essay a brief sketch of secondary education in the medieval Low Countries is given first, with due attention for Donatus's grammar book for the lower grades (finished in the mid-fourth century) and Alexander de Villa Dei's Doctrinale (published in 1199), the teaching manual in common use for advanced pupils. An analysis of two representative samples (Imitaio, I.3.6-9 and IV.1.1-14) proves beyond doubt that Thomas depended for his figurative language on figures of speech in the Doctrinale.